Effects of interplay between metal subwavelength slits on extraordinary optical transmission - 魏菲菲 王怀玉 周云松 (Chinese physics B, 2013)
In this paper we study the extraordinary optical transmission of one-dimensional multi-slits in an ideal metal film.The transmissivity is calculated as a function of various structural parameters.The transmissivity oscillates,with the period being just the light wavelength,as a function of the spacing between slits.As the number of slits increases,the transmissivity varies in one of three ways.It can increase,attenuate,or remain basically unchanged,depending on the spacing between slits.Each way is in an oscillatory manner.The slit interaction responsible for the oscillating transmission strength that depends on slit spacing is the subject of more detailed investigation.The interaction most intuitively manifests as a current distribution in the metal surface between slits.We find that this current is attenuated in an oscillating fashion from the slit corners to the center of the region between two adjacent slits,and we present a mathematical expression for its waveform.